1994
DOI: 10.1148/radiology.190.1.8259423
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis: CT and US correlation in 100 patients.

Abstract: CT is more accurate than US in diagnosis of acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
151
4
16

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(180 citation statements)
references
References 0 publications
9
151
4
16
Order By: Relevance
“…The inflamed appendix is a noncompressible, tubular structure that shows no peristalsis in the longitudinal view. A transverse diameter of more than 6 mm is a reproducible index suggesting appendicitis (21,22). The reported sensitivity of US in diagnosing acute appendicitis ranges from 75% to 90%, the specificity and accuracy are greater than 90% (20,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inflamed appendix is a noncompressible, tubular structure that shows no peristalsis in the longitudinal view. A transverse diameter of more than 6 mm is a reproducible index suggesting appendicitis (21,22). The reported sensitivity of US in diagnosing acute appendicitis ranges from 75% to 90%, the specificity and accuracy are greater than 90% (20,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported CT to be even more accurate than US (21). Balthazar et al (21) prospectively studied, with CT and US, 100 consecutive patients suspected of having appendicitis. Analysis of the data for CT and US revealed sensitivity of 96% vs. 76%, specificity of 89% vs. 91%, and accuracy of 94% vs. 83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scans can be performed without contrast agent [25], with orally and intravenously administered contrast agent [26], with contrast agent applied by oral and colonic routes [27], and with colonically administered contrast medium only [21]. Orally and colonically administered contrast materials yield a high diagnostic accuracy as well as the identification of alternative diagnoses in 80% of cases [27].…”
Section: Right Lower Quadrant Painmentioning
confidence: 99%